A ferroelectric photocatalyst Ag10Si4O13 with visible-light photooxidation properties. Issue 28 (30th June 2016) - Al-keisy, Amar; Ren, Long; Cui, Dandan; Xu, Zhongfei; Xu, Xun; Su, Xiangdong; Hao, Weichang; Dou, Shi Xue; Du, Yi
Abstract : A new ferroelectric p-block photocatalyst, Ag10 Si4 O13, has been successfully prepared here and exhibited excellent visible-light-driven photocatalytic activity towards the degradation of organic compounds. Abstract : Ferroelectric p-block semiconductors are regarded as a new family of visible-light photocatalysts because of their dispersive and anisotropic band structures, as well as their intrinsic internal electric field. Silver silicates belong to this family and have band structures and an internal electric field that can be engineered by modulating the stoichiometry of Ag and SiO4 . Here, we have developed a new ferroelectric p-block photocatalyst, Ag10 Si4 O13, by materials design and band engineering, which exhibits excellent photocatalytic activity towards the degradation of organic compounds, which is driven by visible light. Owing to the unique d 10 and sp/p configurations in its electronic structure, Ag10 Si4 O13 possesses an indirect band gap of 1.72 eV with a highly dispersive conductive band and a flat valence band. This electronic structure promotes the generation, separation, and mobility of photo-induced charge carriers under visible-light illumination, which has been verified experimentally and theoretically. The compatible energy level of the conduction band determines its strong photo-oxidative capability. Moreover, the charge transfer process takes advantage of the existence of an internal electric field in Ag10 Si4 O13, which is attributed to the distorted SiO4 chain structure.